Partitioning of platinum-group elements (PGE) and chalcogens (Se, Te, As, Sb, Bi) between monosulfide-solid solution (MSS), intermediate solid solution (ISS) and sulfide liquid at controlled fO2–fS2 conditions - Liu, Yanan; Brenan, James (Geochimica et cosmochimica acta, 2015)
In order to better understand the behavior of highly siderophile elements (HSEs: Os, Ir, Ru, Rh, Pt, Pd, Au, Re), Ag, Pb and chalcogens (As, Se, Sb, Te and Bi) during the solidification of sulfide magmas, we have conducted a series of experiments to measure partition coefficients (D values) between monosulfide solid solution (MSS) and sulfide melt, as well as MSS and intermediate solid solution (ISS), at 0.1MPa and 860–926°C, log fS2 −3.0 to −2.2 (similar to the Pt–PtS buffer), with fO2 controlled at the fayalite–magnetite–quartz (FMQ) buffer. The IPGEs (Os, Ir, Ru), Rh and Re are found to be compatible in MSS relative to sulfide melt with D values ranging from ∼20 to ∼5, and DRe/DOs of ∼0.5. Pd, Pt, Au, Ag, Pb, as well as the chalcogens, are incompatible in MSS, with D values ranging from ∼0.1 to ∼1×10−3. For the same metal/sulfur ratio, D values for the IPGEs, Rh and Re are systematically larger than most past studies, correlating with higher oxygen content in the sulfide liquid, reflecting the significant effect of oxygen on increasing the activity coefficients for these elements in the melt phase. MSS/ISS partitioning experiments reveal that Ru, Os, Ir, Rh and Re are partitioned into MSS by a factor of >50, whereas Pd, Pt, Ag, Au and the chalcogens partition from weakly (Se, As) to strongly (Ag, Au) into ISS. Uniformly low MSS- and ISS- melt partition coefficients for the chalcogens, Pt, Pd, Ag and Au will lead to enrichment in the residual sulfide liquid, but D values are generally too large to reach early saturation in Pt–Pd-chalcogen-rich accessory minerals, based on current solubility estimates. Instead, these phases likely precipitate at the last dregs of crystallization. Modeled evolution curves for the PGEs and chalcogens are in reasonably good agreement with whole-rock sulfide compositions for the McCreedy East deposit (Sudbury, Ontario), consistent with an origin by crystallization of MSS, then MSS+ISS from sulfide magma.